Book review: "Check mate for Tourism and Tourismology" - Barretto, Margarita (2007)
Review of OURIQUES, Ricardo Helton. A produção do Turismo: fetichismo e dependência. Campinas: Alínea, 2005, 199p. (ISBN 85-7516-106-7).